(untitled) (Agricultural Engineering, 2020)
In 2020, a fully automated hydropower plant was launched on the Guber River near the town of Kotkowo. The plant is operated by a master control and measurement system, which collects data to evaluate the operation of selected systems of the facility. The number and location of sensors controlling the parameters of hydroelectric systems are selected accordingly, to collect complete information from all sensors and analyze the operation of hydroelectric systems in real time. In addition, storing all the controlled parameters allows analyzing the plant’s operation over longer periods. This work presents the possibilities of this measurement system, as well as the measurement results obtained in the tested object. Analyzing the operation of the control and measurement system as well as the collected and archived data will be the foundation for a simulation model of a hydropower plant. The model will be helpful in optimizing the operation of existing hydroelectric plants in terms of energy production per unit volume of water, and in designing new ones on existing barrage.